IMPLEMENTASI METODE TADABBUR AL-QUR’AN DI PESANTREN AR-RAHMAN BOGOR - Syamsuar Hamka (al-Iltizam: Jurnal Pendidikan Agama Islam, 2021)
This research is a case study of qualitative research that aims to describe the Implementation of Tadabbur Method in Qur'anic Learning at Pesantren Ar-Rahman, Megamendung, Bogor. The scopes of this research are 1) The Concept of Tadabbur Method in Qur'anic Learning. 2). Implementation of Tadabbur Method in Qur'anic Learning at Pesantren ar-Rahman. Data collection is carried out by participatory observations and interviews with the director, teachers and students. The results of observations are processed through selection, classification, and direction so as could be concluded. Afterwards the data would be  presented and analyzed to get the description of the Concept and Implementation of the Tadabbur Method in Qur'anic learning. From this research, it was obtained the description that the Implementation of Tadabbur Method in Qur'anic learning at Pesantren ar-Rahman is held on the weekly learning (Ta’lim Rutin Pekanan), where the implementation begins with preparation of tools and learning materials by ‘mudarris’, then continued with tadabbur motivation lifted from a couple of Qur'anic verses. Afterwards, reading the objective verse, write it down and mudarris would be explaining a brief interpretation and the meaning of its certain vocabulary. Then continued with appreciation (penghayatan), go deep into (pendalaman) the verses by optimizing the mind and heart, subsequently writing the wisdom that was obtained.